Physico-mechanical, thermal and morphological properties of furfuryl alcohol/2-ethylhexyl methacrylate/halloysite nanoclay wood polymer nanocomposites (WPNCs) - Md Rezaur, Rahman; Sinin, Hamdan; Chang, Josephine Hui Lai; Jawaid, M.; Fahmi Asyadi, Bin Md Yusof (Elsevier Ltd, 2017)
In this study, the physical, morphological, mechanical and thermal properties of furfuryl alcohol/2-ethylhexyl methacrylate/halloysite nanoclay wood polymer nanocomposites (FA-co-EHMA-HNC WPNCs) were investigated. FA-co-EHMA-HNC WPNCs were prepared via an impregnation method and the properties of the nanocomposites were characterized through the weight percent gain, Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), three-point flexural test, dynamic mechanical thermal analysis (DMTA), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) analysis and moisture absorption test. The weight percent gain in the 50:50 FA-co-EHMA-HNC WPNC was the highest compared with the raw wood (RW) and other WPNCs. The FT-IR results confirmed that polymerization took place in the nanocomposites, especially 50:50 FA-co-EHMA-HNC WPNC, which had a reduced amount of hydroxyl groups. The SEM results revealed that the 50:50 FA-co-EHMA-HNC WPNC had the smoothest and most uniform surface among all of the nanocomposites. The 50:50 FA-co-EHMA-HNC WPNC showed the highest flexural strength and modulus of elasticity. The results revealed that the storage modulus and loss modulus of the FA-co-EHMA-HNC WPNCs were higher and the tan δ of FA-co-EHMA-HNC WNPCs was lower compared with the RW. The FA-co-EHMA-HNC WPNCs exhibited the higher thermal stability in the TGA and DSC analysis. The 50:50 FA-co-EHMA-HNC WPNC exhibited remarkably lower moisture absorption compared with the RW. Overall, this study proved that the ratio 50:50 FA-co-EHMA ratio was the most suitable for introduction in the in the RW. © 2017 The Authors.